A meta-analysis of urban and peri-urban agriculture and forestry in mediating climate change (2015)
This paper systematically reviews literature on urban and peri-urban agriculture and forestry (UPAF) in mediating climate change. The study includes both peer-reviewed and grey literature (274 literature sources), and synthesizes evidence and agreement on both UPAF’s potential and limitations for mitigating and adapting to climate change. Eight East and West African cities were included in the review: Accra, Addis Ababa, Dakar, Dar es Salaam, Douala, Kampala, Ibadan and Nairobi. The review focuses on urban livelihoods, ecosystem services and urban policy responses as pathways to mediating climate change. Literature on UPAF indicates emerging consensus on the potential of UPAF in adaptation, but less agreement with respect to mitigation of climate change. African cities are implementing several measures including UPAF to address issues of development, reduce inequality and move towards low emissions development strategies. This calls for integrated urban development that supports green growth to harness economic opportunities with social and environmental benefits. The review reveals that through UPAF, the potential for mitigation and adaptation of climate change can address some development deficit issues and transform institutions at the city-regional level by leveraging good UPAF practices.